The thirteenth international childhood acute lymphoblastic leukemia workshop report: La Jolla, CA, USA, December 7–9, 20111. Issue 2 (28th September 2012) - Hunger, Stephen P.; Baruchel, Andre; Biondi, Andrea; Evans, William E.; Jeha, Sima; Loh, Mignon; Moericke, Anja; Pieters, Rob; Relling, Mary V.; Schmiegelow, Kjeld; Schrappe, Martin; Silverman, Lewis B.; et al.
Abstract XXX. Pediatr Blood Cancer